Alkylations of functionalized organozinc reagents with allylic epoxides catalyzed by a cyanocuprate - Lipshutz, BH; Woo, K; Gross, T; Buzard, DJ; Tirado, R (GEORG THIEME VERLAG, 1997)
Transmetalation of a functionalized organozinc reagent with 5-10 mol % Me2Cu(CN)Li-2 or MeCu(CN)Li leads to a cyanocuprate which selectively transfers the desired ligand in an S(N)2' sense to allylic epoxides.
Keywords: KETONES